Analisis Penerimaan Penggunaan Aplikasi Antrian Online pada Mal Pelayanan Publik Sidoarjo berdasarkan Unified Theory of Accepptance and Use of Technology (UTAUT) - Silvia Nilam Sari; Widhy Hayuhardhika Nugraha Putra; Bondan Sapta Prakoso (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
The Government of Sidoarjo city built the Mal Pelayanan Publik (MPP) which was inaugurated on January 29, 2019 and implemented an e-government service called Antrian MPP Sidoarjo to facilitate the people who would visit MPP Sidoarjo. Based on the rating of their application on Google Play Store in 2019, Antrian MPP Sidoarjo application gets 3.1 out of 5 stars, and the information centre stated that people still rely on offline queue. This research aims to describe the acceptance of Sidoarjo Regency community towards Antrian MPP Sidoarjo application based on the Unified Theory of Acceptance and Use of Technology (UTAUT) model, which includes performance expectancy, effort expectancy, social influence, and behavioral intention variables. Data collection was carried out by distributing offline questionnaires to 60 samples based on purposive sampling criteria. The data obtained were processed with descriptive statistics and the results showed that the acceptance of Sidoarjo Regency community towards the Antrian MPP Sidoarjo application based on the UTAUT model is quite high (66.75%). There are three variables which values are below the average, namely effort expectancy, social influence, and behavioral intention. As a recommendation, the three variables must be improved or optimized for future implementation. A total of 10 recommendations are given for each indicator of the respective variable.